Analysis of Administration Services in the Regional Office of the Ministry of Religion, Aceh Province - Ismail Ismail (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Service is an effort given by a group of individuals or bureaucracy to provide assistance to the community in order to achieve a certain goal. Improving the quality of administrative services is a very important issue. This happens because the demands of the community for the quality of services are increasingly greater, while the practice of service delivery sometimes does not experience significant changes. The community at all times demands quality services, even though these demands are often not in line with expectations because the services they obtain are sometimes convoluted, slow, expensive and tiring. The formulation of the problem in this study is how the administrative services at the Office of the Ministry of Religion of Aceh Province and the efforts made by the Ministry of Religion of the Province of Aceh in improving administrative services. The method used in this study is a qualitative method, while data collection techniques are done through in-depth observation and interviews with informants. Data collected through observation, interviews and also study documentation. The results of the study relating to administrative services at the Office of the Ministry of Religion in Aceh showed that there were reliable human resources at the Office of the Ministry of Religion in the Province of Aceh and had a sense of responsibility in providing various services in accordance with the workload of each employee. Meanwhile, related to the various efforts made by the Ministry of Religion of the Province of Aceh, both related to capacity building and disciplinary improvement, it still needs to be improved. The conclusion of the research shows that the administrative services at the Office of the Ministry of Religion in Aceh Province are good, but are still slow and the quality needs to be improved. Efforts made by the Ministry of Religion of the Province of Aceh to improve services are related to improving the ability to run well. Whereas related to discipline both regarding timeliness and work facilities are still poor and need to be improved.